PERAN KEPOLISIAN DALAM PENANGANAN PERKARA TINDAK PIDANA OPLOSAN GAS LPG BERSUBSIDI DI POLRES SUKABUMI - Andreas Sinaga, Stiven; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The government is making efforts to ensure that gas energy can be enjoyed by all levels of society. Energy subsidies are the state's efforts to support equitable development. One of the energies that society needs is subsidized LPG gas. Which is gas that is allocated by the state for the poor, in the implementation of its distribution there are certain LPG agents or distributors who commit unlawful acts, namely mixing gas to gain personal profit, one of which occurs in the jurisdiction of the Sukabumi Police. The author attempts to conduct research with the aim of finding out how the law is implemented and enforced, both administratively and criminally, against perpetrators of smuggling government-subsidized LPG gas which occurs in the Sukabumi Police jurisdiction. In carrying out this research, a normative juridical method approach was used using qualitative analysis examining secondary data from previous researchers, regulations and laws and other legal sources. The results of this research are that the transfer and injection of 3 Kg subsidized LPG gas into 12 Kg LPG gas cylinders is work that is prohibited because it does not comply with specified standards, with threats as intended in Article 62 paragraph 1 of Law Number 8 of the Year 1999 Concerning Consumer Protection, they are punished with a maximum imprisonment of 5 (five) years or a maximum fine of IDR 2,000,000,000.00 (two billion rupiah).